Implementasi dan Penggunaan Algoritma Base64 dalam Pengamanan File Video - Supiyandi Supiyandi; Hermansyah Hermansyah; Khairani A P Sembiring (STMIK Budi Darma, 2020)
Personal data is often the target of people who are not responsible for being misused. Theft is done is to benefit from people who have the data. In addition to theft of work files, theft is also carried out on video files. Theft of this file aims to find out what the contents of the video. Someone has a private recorded video that cannot be known by others. Misuse of video files will be fatal for the owner of the video. Cryptographic techniques are needed in video security. Caesar Cipher's algorithm can help users secure the video file. The Base64 algorithm can be used to change the ASCII 256 format to Base64 so that it is easy to send or store in a storage medium. This algorithm will make the file structure simpler so that it can be displayed and saved. By applying the Base64 and Caesar Cipher algorithms to video files, the security and confidentiality of these files will be guaranteed